CHARACTERISTICS OF THE TOPOGRAPHY AND GEOLOGY OF VUNG MAY SEA MOUNTAIN AREA, TRUONG SA, VIETNAM - Thanh, Phi Truong; Hung, Duong Quoc; Diep, Nguyen Van; Nam, Le Dinh (Vietnam Journal of Marine Science and Technology, 2017)
Using the REFLEXW software, Ver. 6.0, analysis and processing of high resolution shallow seismic data of 13 cross section profiles in the Vung May sea mountain area, the analytical results have divided the boundaries of the reflected layers on the top surface and slope of sea mountain at each cross section, corresponding to the boundary of the sediment layers based on the stratigraphy and the results of previous studies in the study area and adjacent areas. In addition, the analytical results also determined the depth values and coordinate of the seabed surface on each section, as the basis to build the 3D model of sea mountain surface and draw the topographic cross sections to calculate the slope angle at each position on the surface around the sea mountain. Based on the geomorphological characteristics and slope angle, the sea mountain surface is divided into three parts: Top surface, slope surface and foot surface. Each part of the sea mountain has separate geological and geomorphological features. At the top surface, the topography has lagoon-shaped form, surrounded by elevated edge. The size of the lagoon is about 45 km long, 20 km wide, 10 - 40 m deep and slope angle is smaller than 0.5 degrees (< 0.5o). On the slope surface, topography is divided into two parts: The first one lies at a depth from the upper flank to -750 m deep, slope angle is within 8 - 20o; the second one lies at a depth from -750 m to -1,400 ¸ -1,500 m, slope angle is smaller, varies in the range of 4 - 10o. At the foot of sea mountain, the terrain is a large area, at the depth of -1,400 ¸ -1,500 m with slope angle within 1 - 5o. The results obtained in this study are consistent with previous studies in the area and adjacent areas